Pattern of adverse drug reactions reported by the community pharmacists in Nepal - Palaian S; Ibrahim MIM; Mishra P (Pharmacy Practice, 2010)
The pharmacovigilance program in Nepal is less than a decade old, and is hospital centered. This study highlights the findings of a community based pharmacovigilance program involving the community pharmacists. Objectives: To collect the demographic details of the patients experiencing adverse drug reactions (ADR) reported by the community pharmacists; to identify the common drugs causing the ADRs, the common types of ADRs; and to carry out the causality, severity and preventability assessments of the reported ADRs. Methods: The baseline Knowledge-Attitude-Practices (KAP) of 116 community pharmacists from Pokhara valley towards drug safety was evaluated using a validated (Cronbach alpha=0.61) KAP questionnaire having 20 questions [(knowledge 11, attitude 5 and practice 4) maximum possible score 40]. Thirty community pharmacists with high scores were selected for three training sessions, each session lasting for one to two hours, covering the basic knowledge required for the community pharmacists for ADR reporting. Pharmacist from the regional pharmacovigilance center visited the trained community pharmacists every alternate day and collected the filled ADR reporting forms. Results: Altogether 71 ADRs, from 71 patients (37 males) were reported. Antibiotics/ antibacterials caused 42% (n=37) of the total ADRs followed by non steroidal anti-inflammatory drugs [25% (n=22)]. Ibuprofen/paracetamol combination accounted for ten ADRs. The most common type of ADR was itching [17.2 % (n=20), followed by generalized edema [8.6 % (n=10)]. In order to manage the ADRs, the patients needed medical treatment in 69% (n=49) of the cases. Over two third (69%) of the ADRs had a ‘possible’ association with the suspected drugs and a high percentage (70.4%) were of ‘mild (level 2)’ type. Nearly two third [64.7 % (n=46)] of the ADRs were ‘definitely preventable’. Conclusion: The common class of drugs known to cause ADRs was antibacterial/ antibiotics. Ibuprofen/ Paracetamol combination use of the drug was responsible for more number of ADRs and the most common ADRs were related to dermatological system. Strengthening this program might improve safe use of medicines in the community.